Association Between Parenting and School Refusal Among Elementary School Children in Japan: Results From A-CHILD Longitudinal Study - Fukuya, Yoshifumi; Fujiwara, Takeo; Isumi, Aya; Doi, Satomi; Ochi, Manami (Frontiers in Pediatrics, 2021)
Objective: The aim of this study was to examine the association between parenting, including parent-child interaction and child maltreatment in first grade (6-7 years old), and school refusal in second (7-8 years old) and fourth grade (9-10 years old) among elementary school children in Japan. Methods: Data were from the Adachi Child Health Impact of Living Difficulty (A-CHILD) longitudinal study conducted in 2015, 2016, and 2018 in Adachi City, Tokyo, Japan. A questionnaire was distributed to all first-grade school children (N=5,355) in 2015. Of the total 4,291 valid children (response rate: 80.1%), 3,590 and 3,070 children were followed up to second and fourth grade, respectively. Caregivers responded to the questionnaire on parent-child interaction and child maltreatment, including neglect, physical abuse, and psychological abuse in first grade and school refusal in second and fourth grade. We conducted multiple imputation for missing data. Multivariate logistic regression model was used for this analysis adjusting for child mental health in first grade and sociodemographic characteristics. Results: Prevalence of school refusal was 1.8 % (n=64) in second grade and 2% (n=60) in fourth grade. We found no association of parent-child interaction and child maltreatment in first grade with school refusal in second and fourth grade, respectively, after adjusting for covariates. Conclusions: Parenting, such as parent-child interaction and child maltreatment, may not be associated with school refusal among elementary school children. Further longitudinal research is needed to elucidate other factors, such as peer relationships and school environment, which can affect school refusal.